Terapi Kognitif Perilaku dan Defisit Perawatan Diri : Studi Literatur - Robby Prihadi Aulia Erlando (ARTERI : Jurnal Ilmu Kesehatan, 2019)
People with mental disorders have difficulty to fulfill their needs. This can be caused by a decrease in the ability possessed by ODGJ. Decreased ability possessed by ODGJ can be the ability to care for themselves such as bathing, eating, dressing and making up themselves. Limit of the information and inability of the family will affect the actions taken on ODGJ for example in terms of fulfill their daily needs. The client's needs include physical and psychological needs, both of which need to be cared for and met according to portions. Meeting the physical needs of ODGJ needs to be considered because it will be directly proportional to the psychological fulfillment of the client, if not met then it can worsen the client's condition. The family's decision to apply pasung on the clients will affect the client's ability to care for himself. Writing this manuscript aims to see the condition of clients with self-care deficits who do not believe that self-care is very important in addition to other therapeutic measures related to mental health. This manuscript examines cognitive and behavioral therapy for self-care deficit cases. This method is carried out by reviewing journals related to the application of cognitive and behavioral therapies, self-care deficits and factors that can influence the outcome of the administration of therapy. The best experience can be obtained by the client if the client is directly involved in getting enough information about the importance of maintaining personal hygiene, knowing how to do it and being able to apply it to daily activities.